Semantic processing during continuous speech production: an analysis from eye movements and EEG - Huang, Jinfeng; Zhang, Gaoyan; Dang, Jianwu; Chen, Yu; Miyamoto, Shoko (Frontiers in Human Neuroscience, 2023)
Speech production encompasses both neurological planning and articulatory execution. A crucial issue in the study of speech production is how speakers prepare for articulation. Previous studies have primarily utilized isolated words or short phrases to investigate the mechanism of speech planning associated with articulatory behaviors, such as by investigating the eye-voice span (EVS) during text reading. However, these experimental paradigms fail to replicate the natural speech process in real-world scenarios. Furthermore, our understanding of the neurological aspect of speech planning remains limited. This study delves into the mechanisms of speech planning during continuous speech production by examining behavioral (eye movement and speech) and neurophysiological (EEG) data during a continuous speech production task. Specifically, we explore the impact of semantic consistency on speech planning and the occurrence of "look ahead" behavior. The results demonstrate that semantic coherence plays a critical role in producing fluent speech, with speakers accessing lexical representations and phonological information prior to initiating utterances. The behavioral findings indicate that the EVS progressively decreases during ongoing reading of regular sentences, but slightly increases for non-regular sentences. Additionally, the analysis of eye movement patterns suggests two distinct modes of speech production and underscores the significance of semantic comprehension and prediction in higher-level lexical processing. The analysis of neural data supports the dual pathway model of speech production, revealing a dorsal information flow and involvement of the frontal lobe. Additionally, the brain network implicated in processing semantic understanding shows a negative correlation with semantic coherence, with significant activation occurring only during semantic incoherence, and being suppressed in regular